Taking Religious Claims Seriously A Philosophy of Religion. Edited by Michael H. Mitias - Steinkraus, Warren E. (Religious Studies, Theology and Philosophy - Book Archive pre-2000., 1998)
Taking Religious Claims Seriously is a systematic, critical, and comprehensive study of the fundamental questions of the philosophy of religion: religious experience, the existence and nature of God, religious knowledge and truth, good and evil, immortality of the soul, religious diversity, religious claims about the person, faith, and the religious way of life. In this study the author seeks to capture the reality and meaning of the religious as such: What is the foundation of religion? Under what conditions is an authentic religious way of life possible? His method of inquiry is phenomenological. The author begins his discussion with a general characterization of the basic features of all the literate and illiterate religions of the world. He then identifies the ideas, beliefs, and concerns which are common to these religions: What are the central claims of these religions? How did the various religions understand these claims? The author makes a serious attempt to clarify these claims and explore the possibility for a reconcilation between them. For him, the foundation of religion is the religious experience, and the essence of this experience consists in a serious, cognitive, and meaningful encounter with the Ultimate Being. This being is the ground of the world and human life. This book is a comparative, pluralistic study of the philosophy of religion.